ANALISIS KUALITAS AUDIT DAN PERTUMBUHAN PENJUALAN TERHADAP KEWAJIBAN PAJAK DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Sagita, Dian Maya (EAJ (Economic and Accounting Journal), 2019)
The company still considers the obligation to pay taxes a burden because there is a transfer of resources from the business sector to the public or government sector so that management often makes various efforts to minimize the tax burden, even though the compliance of taxpayers in paying taxes will assist the government in conducting programs development that can be enjoyed by the citizen. This study aimed to analyze the effect of audit quality and sales growth on tax obligations with earnings management as an intervening variable. The population in this study were all property and real estate companies listed on the Indonesia Stock Exchange in 2013-2017. The sample was selected using a purposive sampling method and obtained 100 units of analysis. The analytical method used is descriptive statistical analysis and path analysis (path analysis) using IBM SPSS 24 application. The results showed that audit quality and sales growth did not significantly influence earnings management either partially or simultaneously. Furthermore, the audit quality variable does not have a significant effect on tax obligations, but the sales growth variable shows a significant positive effect on the tax liability variable. The results of the path analysis test show that each variable of audit quality and sales growth has no effect on tax liabilities through earnings management as a mediating variable. The conclusion of this study is the amount of tax liability borne by the company is influenced by the level of sales growth.